SOCIAL ACTIVITY OF THE RUSSIAN YOUTH: THE SCOPE AND RESTRAINING FACTORS - Sokhadze, K.G. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2017)
In recent years, both experts and public opinion tend to assess the involvement of the Rus-sian youth in social activities as rather low: the post-Soviet generations are called apolitical and indifferent to anything except personal well-being and interests. At the same time, the largest research centers (Public Opinion Foundation, Russian Public Opinion Research Center, Levada Center, and Institute of Sociology) conduct sociological studies of various aspects of social and civil activities, political participation and protest potential of younger generations and Russian society as a whole. The article presents some recent data that prove the low level of political and social activity of the Russian population. The author believes that this level is higher among the younger generations, especially the students. To prove that, first, the author considers the category ‘social activity’: its motives (primarily socially significant needs), subjective ‘measurement’ (personal needs and interests), goals (pragmatic and altruistic, collective and personal, etc.), forms (personal, collective, etc.) and external and internal factors. Secondly, to assess the motives and restraining factors of the youth social activity, the article presents some results of the surveys conducted in the RUDN University and of the Russian public opinion polls. The author identifies reasons for the youth’s lack of interest in public activities (lack of material benefits, desire/time/motivation, information, and nega-tive image of public associations), motives of social activity (social, selective, mobilization, etc.) and for be-coming a member of public associations (self-realization, the desire to change the world, combination of the two, etc.), and factors that determine the youth’s perception of social activity in general (estimates of so-cial situation, value orientations and social well-being).